Answer:
{[tex](x,y)|(x=3,y=4)[/tex]}
Step-by-step explanation:
The given system of equations is;
[tex]y-4=0...(1)[/tex]
and
[tex]2x-y-2=0...(2)[/tex]
We rewrite the equations in the standard form to get:
[tex]y=4...(3)[/tex]
[tex]2x-y=2...(4)[/tex]
We now substitute equation (3) into equation (4) to get:
[tex]2x-4=2[/tex]
Group similar terms:
[tex]2x=2+4[/tex]
[tex]2x=6[/tex]
Divide both sides by 2
[tex]\frac{2x}{2}=\frac{6}{2}[/tex]
This implies that:
[tex]x=3[/tex]
Therefore the solution set is:
{[tex](x,y)|(x=3,y=4)[/tex]}